Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2019
DOI: 10.1007/s11356-019-06985-z
|View full text |Cite
|
Sign up to set email alerts
|

An energy-based model to analyze growth data of earthworms exposed to two fungicides

Abstract: The pesticide risk assessment for earthworms is currently performed using standardized tests, the model species Eisenia fetida, and the analyses of the data obtained are performed with ad hoc statistical tools. We assessed the impact of two fungicides on the entire growth pattern of the earthworm species Aporrectodea caliginosa, which is highly representative of agricultural fields. Individuals of three different ages (from hatching to 56 days old) were exposed to Cuprafor micro ® (copper oxychloride) and Swin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 55 publications
1
5
0
Order By: Relevance
“…Big anecic earthworms such as A. giardi, A. longa, or L. terrestris which feed at the soil surface and live in the subsoil, are highly exposed to the bioavailable fraction of pesticides and would inevitably take longer time to recover (Mombo et al, 2018;Pelosi et al, 2014). The results on A. caliginosa observed in this study were in line with previous studies revealing its sensitivity to pesticides (Bart et al 2018;Pelosi et al, 2013b) and metals (Khalil et al, 1996;Maity et al, 2018) in general, and to these contaminants in particular (Bart et al, 2017(Bart et al, , 2019(Bart et al, , 2020. The sensitivity of A. chlorotica (the green morph, as identified in the present study) to pesticides has already been highlighted in a field-based study (Pelosi et al, 2013b), and related to its habitat as it is commonly found in the top 5 cm of the soil.…”
Section: Species Sensitivity and Recoverysupporting
confidence: 90%
See 2 more Smart Citations
“…Big anecic earthworms such as A. giardi, A. longa, or L. terrestris which feed at the soil surface and live in the subsoil, are highly exposed to the bioavailable fraction of pesticides and would inevitably take longer time to recover (Mombo et al, 2018;Pelosi et al, 2014). The results on A. caliginosa observed in this study were in line with previous studies revealing its sensitivity to pesticides (Bart et al 2018;Pelosi et al, 2013b) and metals (Khalil et al, 1996;Maity et al, 2018) in general, and to these contaminants in particular (Bart et al, 2017(Bart et al, , 2019(Bart et al, , 2020. The sensitivity of A. chlorotica (the green morph, as identified in the present study) to pesticides has already been highlighted in a field-based study (Pelosi et al, 2013b), and related to its habitat as it is commonly found in the top 5 cm of the soil.…”
Section: Species Sensitivity and Recoverysupporting
confidence: 90%
“…It is worth specifying that the field studies with earthworms reported in EFSA scientific report (2005) were conducted because a high long-term risk to earthworms was identified in a first-tier risk assessment under laboratory conditions (NOEC reproduction 56 days <0.0887 mg DMX a.s. kg -1 soil). Moreover, under laboratory conditions, Pelosi et al (2016) and Bart et al (2019Bart et al ( , 2020 reported negative impacts of these fungicides (EPX applied alone or EPX+DMX in the Swing® Gold formulation) on the biochemical response to oxidative stress of A. icterica, and on the growth and reproduction of A. caliginosa at realistic concentrations. The Swing® Gold fungicide at three times the RR (0.465 mg DMX kg −1 and 0.174 mg EPX kg −1 ) decreased the cocoon production of A. caliginosa by 63%, and the hatching success significantly decreased by 16% at the RR (0.155 mg DMX kg −1 and 0.0581 mg EPX kg −1 ) (Bart et al, 2020).…”
Section: Impacts Of the Tested Fungicides On Earthworm Communities Over Two Yearsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, this fungicide could have had negative effects on enchytraeid reproduction because its EC50 (effective concentration that induced a 50% decrease) for E. albidus reproduction was estimated at only 1.66-fold the recommended field rate (Bart et al 2018). In addition, Swing® Gold fungicide was reported to negatively affect the growth of A. caliginosa, with a NEC (no effect concentration) value estimated at 2.5-fold the recommended field rate (Bart et al 2020), which is below the dose used in the SG3 treatment group in this study. However, the authors reported that (i) the magnitude of the effects depended on the exposure age (with stronger effects on bigger juveniles of 300 mg than on juveniles of 10-20 mg, as used in our experiment), and (ii) the active substances dissipated in soil over time and can reach lower concentrations than the NEC during the experiment (15 days after the start of the exposure in Bart et al 2020, with the same soil and temperature conditions as in our study).…”
Section: Discussionmentioning
confidence: 56%
“…Therefore, mixture effect assessment needs diagnostic tools that account for these temporal aspects. To explain and predict the effects of mixtures, toxicokinetic–toxicodynamic models (TKTD models), which simulate the time course of processes leading to toxicity, offer a promising approach. Previous studies have presented TKTD models to analyze effects of mixtures on survival that have been successfully applied to mixture datasets. …”
Section: Introductionmentioning
confidence: 99%